Watershed Management in Rainfedareas: Learning from the People - Sharma, D. D.; Sharma, Anita (Indian Forester, 2001)
All the spatial components of land mass viz. arable land, non-arable land and drainage lines are being developed as one organic unit under the project "National Watershed Development Project for Rainfed Areas" which is mainly based on people's indigenous knowledge. Recognising that it is not possible to motivate most of the rural people without economic incentive, the technology comprises of both, the conservation systems and production systems.